Combustion of Boron Particles in Premixed Methane/Air Flames. Issue 2 (4th February 2016) - Veith, Jan; Pfitzner, Michael
Abstract: Because of its high energy density, boron particles have been a subject of interest for the use as propellant in propulsion systems for many years. A cheap and fast opportunity to investigate multiphase reacting flows in such systems is offered by numerical simulations. Therefore, a detailed knowledge of the chemistry and kinetics of boron combustion in different gaseous surroundings is required. The main topic of this contribution is the experimental investigation of the influence of the equivalence ratio of reacting methane‐air mixtures on the combustion time of boron particles. Additionally, numerical calculations were performed using a combustion model proposed by Yeh et al. [1] and modified by Hussmann et al. [2, 3]. The experimental results show that for small particles there exists an optimal stoichiometry, at which the combustion time of boron particles is minimized. High equivalence ratios yield larger burning times because of a low concentration of oxygen. Low equivalence ratios are accompanied by low flame temperatures also leading to large burning times, because of a slow reactive evaporation of the boron‐oxide layer. With increasing particle size the burning process is dominated by the evaporation process. Numerical results are in a good agreement with the experiments for small particles. For larger particles, the predicted burning time is too high due to the fact that boron particles cannot be treated as a sphere as assumed in the original model. By implementing a sphericity factor good agreement with the experiments can be achieved. Abstract :